Southern Society and Its Transformations, 1790-1860 - Kyriakoudes, Louis M.; Gillespie, Michele; Delfino, Susanna, 1949- (New currents in the history of Southern economy and society., 2011)
In Southern Society and Its Transformations, a new set of scholars challenge conventional perceptions of the antebellum South as an economically static region compared to the North. Showing that the pre-Civil War South was much more complex than once thought, the essays in this volume examine the economic lives and social realities of three overlooked but important groups of southerners: the working poor, non-slaveholding whites, and middling property holders such as small planters, professionals, and entrepreneurs.